EFFECTIVENESS OF MAGNESIUM CITRATE ADJUNCTIVE THERAPY ON CRAMPING PAIN INTENSITY IN NOCTURNAL LEG CRAMPS PATIENTS AT BETHESDA HOSPITAL YOGYAKARTA - Digdoyo, Ananda; Pinzon, Rizaldy Taslim; Pramudita, Esdras Ardi (Jurnal Farmasi Sains dan Praktis, 2024)
Nocturnal Leg Cramps (NLC) are involuntary lower limb contractions that are painful and occur during long rest periods. Magnesium is thought to have potential in the treatment of NLC as one of the precipitating factors of NLC is low levels of certain minerals, such as magnesium deficiency. This study aimed to assess the effectiveness of magnesium adjunctive therapy in reducing cramping pain intensity in patients with NLC. This study was a randomized clinical trial, open-label, controlled group that was followed up for 2 weeks. 30 subjects who have been diagnosed with the NLC short-form adaptation of ICSD 2005 were divided into 2 groups; (1) the intervention group who was given standard NLC therapy (calcium and gabapentin) with additional therapy of magnesium citrate 100 mg (Hi-Mg100) one tablet a day, (2) the control group who was only given standard NLC therapy. NLC cramping pain was measured using the Numeric Rating Scale (NRS) before the administration of therapy (baseline) and at week 2 after therapy. The results obtained were the addition of magnesium to standard therapy provided a significant reduction in cramping pain intensity between before and after treatment based on the Wilcoxon signed rank test (p=0.000). However, there was no statistically significant difference effect between the two therapy groups based on the Mann-Whitney test (p=0.073). In conclusion, magnesium adjunctive therapy was not significantly more effective in reducing cramping pain than standard drug therapy in patients with NLC.